Biomarkers for a histological chorioamnionitis diagnosis in pregnant women with or without group B streptococcus infection: a case-control study - Jie Ren; Zhe Qiang; Yuan-yuan Li; Jun-na Zhang (BMC, 2021)
Abstract Background Chorioamnionitis may cause serious perinatal and neonatal adverse outcomes, and group B streptococcus (GBS) is one of the most common bacteria isolated from human chorioamnionitis. The present study analyzed the impact of GBS infection and histological chorioamnionitis (HCA) on pregnancy outcomes and the diagnostic value of various biomarkers. Methods Pregnant women were grouped according to GBS infection and HCA detection. Perinatal and neonatal adverse outcomes were recorded with a follow-up period of 6 weeks. The white blood cell count (WBC), neutrophil ratio, and C-reactive protein (CRP) level from peripheral blood and soluble intercellular adhesion molecule-1 (sICAM-1), interleukin 8 (IL-8), and tumor necrosis factor α (TNF-α) levels from cord blood were assessed. Results A total of 371 pregnant women were included. Pregnant women with GBS infection or HCA had a higher risk of pathological jaundice and premature rupture of membranes and higher levels of sICAM-1, IL-8, and TNF-α in umbilical cord blood. Univariate and multivariate regression analysis revealed that sICMA-1, IL-8, TNF-α, WBC, and CRP were significantly related to an increased HCA risk. For all included pregnant women, TNF-α had the largest receiver operating characteristic (ROC) area (area: 0.841; 95% CI: 0.778-0.904) of the biomarkers analyzed. TNF-α still had the largest area under the ROC curve (area: 0.898; 95% CI: 0.814-0.982) for non-GBS-infected pregnant women, who also exhibited a higher neutrophil ratio (area: 0.815; 95% CI: 0.645-0.985) and WBC (area: 0.849; 95% CI: 0.72-0.978), but all biomarkers had lower value in the diagnosis of HCA in GBS-infected pregnant women. Conclusion GBS infection and HCA correlated with several perinatal and neonatal adverse outcomes. TNF-α in cord blood and WBCs in peripheral blood had diagnostic value for HCA in non-GBS-infected pregnant women but not GBS-infected pregnant women.